2020
DOI: 10.1186/s13063-020-4169-7
|View full text |Cite
|
Sign up to set email alerts
|

Verifying participant-reported clinical outcomes: challenges and implications

Abstract: Background: Researchers often rely on trial participants to self-report clinical outcomes (for example, fractures, reoperations). Little information exists as to the 'accuracy' of participant-reported clinical outcomes, particularly in randomised controlled trials (RCTs). To help address this evidence gap, we report four case studies, nested within different RCTs where participant-reported clinical outcome data were compared with those reported by clinicians or extracted from medical notes. Methods: Four publi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…In parallel, implementation of best-practices to enhance validity of participant-report, including stakeholder engagement in survey design, readability assessments, and cultural and linguistic adaptation are essential to enhancing reliability of findings from participant-facing research. [26][27] Our findings are broadly consistent with those from prior studies suggesting that fitness-for-use depends on context. [28][29] We found that no single data source may be appropriate for EHRbased pragmatic research, consistent with prior work illustrating the potential biases that can arise in participant-reported data and how they vary.…”
Section: Principal Resultssupporting
confidence: 90%
“…In parallel, implementation of best-practices to enhance validity of participant-report, including stakeholder engagement in survey design, readability assessments, and cultural and linguistic adaptation are essential to enhancing reliability of findings from participant-facing research. [26][27] Our findings are broadly consistent with those from prior studies suggesting that fitness-for-use depends on context. [28][29] We found that no single data source may be appropriate for EHRbased pragmatic research, consistent with prior work illustrating the potential biases that can arise in participant-reported data and how they vary.…”
Section: Principal Resultssupporting
confidence: 90%